Closed Circuit Reverse Osmosis a Way to Minimize Brine Waste: (Two Case Studies in Power Plant Water Treatment Units) - Shahram Niazi (آب و فاضلاب, 2023)
Nowadays, lack of water resources has become a crisis in many countries around the world including our country, Iran. In the current situation, minimizing the waste of water is vital. Continuous reverse osmosis system, the most widespread technology for water desalination, wastes large amounts of fresh feed water as high salinity brines. Hydraulic parameters and deposition of salts on the membranes are the most important factors limiting the maximum achievable recovery rates in RO systems. Closed circuit RO technology by modifying the operational mode of continuous RO system to a cyclic semi-batch process, reduces limitations of the maximum possible recovery and can decrease the amount of water waste by 90%. Due to the lack of experience and knowledge about CCRO technology in Iran, the main goal of the present study is the performance evaluation of CCRO systems in Iran's water desalination plants. For this purpose, two industrial RO systems, located in central and northwestern Iran, were selected as case studies. For the first time, according to the real feed water matrix, the maximum achievable recovery of systems was investigated by changing continuous RO to CCRO systems. The results revealed that implementing CCRO systems could significantly decrease brine production rate 74 to 89%. However, the electrical energy consumption of the systems increased reasonably 8 to 36%. For high salinity feed water (1st case study), the maximum allowable operating pressure of membrane 41.4 bar limited the recovery of CCRO system to 88.7%. For the system with low salinity feed 2nd case study, the recovery was limited to 96.6% due to restriction in the maximum permeate flowrate per element (1.58 m3h-1). In this case, the saturation levels of silica and sulfate salts were much higher than the permissible levels. Therefore, dosing a suitable antiscalant and high volumes of sulfuric acid were necessary to control the scaling. However, acid and antiscalant demands were reduced by a decrease in CCRO recovery rate.